The Evaluation of Career and Employment Counselling: A New Direction - Kellett, Ralph (Canadian Journal of Counselling and Psychotherapy, 2007)
The partners that make up the Canadian Labour Force Development Board (CLFDB), which are business, labour, education/training and the employment equity groups, have traditionally viewed career and employment counselling as important. However, information on the availability of career and employment counselling services across Canada has been lacking. There is also little evaluative information to demonstrate the contribution of counselling in helping people make the transition from school to work or unemployment to employment. A survey of career and employment counselling conducted under the sponsorship of the CLFDB showed that little counselling evaluation is being done in the schools, colleges, universities, within community agencies or the Canada Employment Centres. The absence of evaluative information places the service at risk of being discontinued. Those in leadership positions have to be convinced of the need for more and better evaluation of counselling. A new model or models for the evaluation of career and employment counselling is needed, as are new measurement instruments.